Administrative res judicata in Brazilian law: public administration and the constitutional principle of legal certainty - Klein Gussoli, Felipe (Universidad Nacional del Litoral, 2017)
In Brazil there is no consensus on the administrative res judicata. While some preach their absence in the Brazilian law system, other host administrative res judicata based on non homogeneous foundations. Thus, the work aims to clarify the concepts and definitions proposed doctrinally and referred to the Public Administration and Courts, for from that extract an innovative definition of administrative res judicata to explain the relevance of the institute in the Brazilian legal system and to justify its practical utility. The methodology is deductive. Starts from the Constitution and takes the administrative res judicata as a corollary of the principles of legal certainty, protection of trust and good faith. The paper analyzes also, in parallel, the system of judicial res judicata to conclude the administrative res judicata as a formal limit to the duty of Administration cancel its ilegal acts, bound to the litigious administrative processes and identifiable according to the Brazilian legal administrative system. The considerations contribute scientifically by demonstrating the Brazilian constitutional locus of administrative res judicata, its incidence substract, its negative, positive and preclusive effects as well as the objective and subjective limits of this unique figure.